2021
DOI: 10.3389/fonc.2021.757167
|View full text |Cite
|
Sign up to set email alerts
|

3D Quantitative Ablation Margins for Prediction of Ablation Site Recurrence After Stereotactic Image-Guided Microwave Ablation of Colorectal Liver Metastases: A Multicenter Study

Abstract: BackgroundThree-dimensional (3D) volumetric ablation margin assessment after thermal ablation of liver tumors using software has been described, but its predictive value on treatment efficacy when accounting for other factors known to correlate ablation site recurrence (ASR) remains unknown.PurposeTo investigate 3D quantitative ablation margins (3D-QAMs) as an algorithm to predict ASR within 1 year after stereotactic microwave ablation (SMWA) for colorectal liver metastases (CRLM).Materials and MethodsSixty-fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Previous studies have used rigid and nonrigid image registration methods to assess the MAM and have reported various optimal cutoff values for MAM to minimize LTP, ranging from 2 to 5 mm. 6,7,12 In this present study, we found that no LTP was noted with an MAM of more than 3.2 mm on intraprocedural CT, which was consistent with previous studies including one from our group that used the same ablation confirmation methodology. 3 However, a cutoff value of 5 mm on MAM quantified on initial follow-up CTwas not a significant predictor for LTP.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have used rigid and nonrigid image registration methods to assess the MAM and have reported various optimal cutoff values for MAM to minimize LTP, ranging from 2 to 5 mm. 6,7,12 In this present study, we found that no LTP was noted with an MAM of more than 3.2 mm on intraprocedural CT, which was consistent with previous studies including one from our group that used the same ablation confirmation methodology. 3 However, a cutoff value of 5 mm on MAM quantified on initial follow-up CTwas not a significant predictor for LTP.…”
Section: Discussionsupporting
confidence: 92%
“…1,2 Further, sufficient ablative margin is considered as a critical factor for local tumor control, and several dedicated ablation confirmation methods have been developed to standardize the process of ablative margin quantification. [3][4][5][6][7] Recently, an ablation confirmation method using biomechanical deformable imaging registration method, which takes into consideration the liver's biomechanical properties and deformation after ablation, has been proposed. This method disclosed that a minimal ablative margin (MAM) of ≥5 mm was achieved in less than half of tumors that were ablated with an endpoint of margin ≥5 mm evaluated by visual inspection in a retrospective analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The limited number of PET/CT scanners worldwide and the even smaller number of dedicated PET/CT equipment allowing the presence of anesthesia equipment and staff for image-guided interventions currently impact the utility of this method in most institutions [ 21 ]. Although 3D software is increasingly used and is recommended for the proper assessments of the AZ [ 8 , 34 , 35 ], its widespread availability is still lacking. All software platforms are affected by motion artifacts and extreme positioning differences that impact registration and fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The most important drawback of thermal ablation is the appearance of viable tumour tissue at the edge of the ablation zone [ablation site recurrence (ASR)] [ 10 , 11 ]. Complete tumour coverage with an adequate ablation margin assessed in 3D is crucial for treatment success [ 12 , 13 , 14 , 15 ]. To achieve complete tumour coverage, creation of predictable ablation volumes is essential and depends, among other things, on the applied energy controlled by the power and time setting of the ablation device.…”
Section: Introductionmentioning
confidence: 99%